2016
DOI: 10.3329/ptcb.v26i2.30570
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Flax Drought Tolerance Using Gene Transfer

Abstract: Attempt was made to produce transgenic cell lines of flax cv. Blanka tolerant to drought stress. Genetic transformation systems were used to incorporate the DREB2A gene, as the specific gene for drought stress tolerance. In biolistic transformation, hypocotyl segments were bombarded with DREB2A and GFP genes at particle flight distance of 9 cm and rupture disc pressure of 1300 psi. The expression of the gene was observed under a light microscope after 24 and 48 hrs. In Agrobacterium-mediated transformation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Since 1995, when long-term traditional breeding programs to enhance linseed stress tolerance and improve crop yield under periodic drought, transgenic linseed plants have been obtained for enhancing tolerance to DS [13,14]. Some transgenic linseed plants have been obtained for enhancing tolerance to drought stress [15]. Despite recent advances in linseed drought tolerance, how it functions is another open question PacBio's SMRT (single-molecule real-time) sequencing (PacBio, http://www.paci cbiosciences.com/)…”
Section: Introductionmentioning
confidence: 99%
“…Since 1995, when long-term traditional breeding programs to enhance linseed stress tolerance and improve crop yield under periodic drought, transgenic linseed plants have been obtained for enhancing tolerance to DS [13,14]. Some transgenic linseed plants have been obtained for enhancing tolerance to drought stress [15]. Despite recent advances in linseed drought tolerance, how it functions is another open question PacBio's SMRT (single-molecule real-time) sequencing (PacBio, http://www.paci cbiosciences.com/)…”
Section: Introductionmentioning
confidence: 99%
“…Drought is an erratic and highly unpredictable environmental phenomenon; therefore, selection should target drought tolerant genotypes having yield potential. Accordingly, long-term traditional breeding programs and later development of transgenic flax were initiated to combat these constraints and improve flax production ( Tawfik et al, 2016 ). Since drought tolerance is a complex polygenic trait, understanding the adaptive mechanisms and identification of underlying genes/markers/QTLs could pave a way for genetic enhancement and productivity of flax in arid and semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported overexpression of drought responsive element binding protein 2A (DREB2A) gene imparting drought tolerance in transgenic line of flax cv. Blanka(Tawfik et al, 2016). Similarly, for high temperature stress, few genes have been discovered and functionally characterized in flax.Saha et al (2019) reported the genome-wide identification of 34 putative HSF genes from the flax genome.…”
mentioning
confidence: 99%
“…Since 1995, when long-term traditional breeding programs to enhance linseed stress tolerance and improve crop yield under periodic drought, transgenic linseed plants have been obtained for enhancing tolerance to DS [13,14]. Some transgenic linseed plants have been obtained for enhancing tolerance to drought stress [15]. Despite recent advances in linseed drought tolerance, how it functions is another open question.…”
Section: Introductionmentioning
confidence: 99%